Primary Health Care in the Rural Area of the Islamic Republic of Iran - H Malekafzali (Tehran University of Medical Sciences, 2009)
Primary health care in the Islamic Republic of Iran was conceived and nurtured on the strength of scientific research, political commitment, and well thought out planning. Due to expansion of PHC network in rural areas of Iran health Indicators have significantly improved. The health care and network in this country is, however, in need of serious repair if all this endeavors hither to be wasted.